2016
DOI: 10.1186/s12967-016-0790-3
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-beta 1 produced by vascular smooth muscle cells predicts fibrosis in the gastrocnemius of patients with peripheral artery disease

Abstract: BackgroundLower leg ischemia, myopathy, and limb dysfunction are distinguishing features of peripheral artery disease (PAD). The myopathy of PAD is characterized by myofiber degeneration in association with extracellular matrix expansion, and increased expression of transforming growth factor-beta 1 (TGF-β1; a pro-fibrotic cytokine). In this study, we evaluated cellular expression of TGF-β1 in gastrocnemius of control (CTRL) and PAD patients and its relationship to deposited collagen, fibroblast accumulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 52 publications
9
58
0
Order By: Relevance
“…These deficits appear related to the neuropathy and myopathy previously described by our group 24,11,2728 and others. 56,3133 Our work demonstrates that there are functional tests, including the maximal isometric plantar flexion test we are describing in this paper, that can measure and stratify the degree of impairment in the legs of patients with PAD.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These deficits appear related to the neuropathy and myopathy previously described by our group 24,11,2728 and others. 56,3133 Our work demonstrates that there are functional tests, including the maximal isometric plantar flexion test we are describing in this paper, that can measure and stratify the degree of impairment in the legs of patients with PAD.…”
Section: Discussionsupporting
confidence: 79%
“…The strength differences between Controls and PAD when subjects perform a 10 seconds isometric test immediately after rest and before any exercise-induced ischemia/pain confirm that the weakness in the PAD ankle plantar flexors is related to the well described myopathy of PAD. 2,4,9,11,2728 Furthermore, the introduction of ischemic claudication symptoms altered the motor control strategies of the ankle plantar flexors producing significant differences between PAD conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has suggested a detrimental role of TGFβ signaling in the progression of PAD by measuring the levels of TGFβ and its receptors in ischemic tissues and in peripheral blood collected from patients [104106]. We are interested in the effect of TGFβ-induced TSP-1 synthesis and potential interventions to reduce TSP-1 in both normoxic and hypoxic conditions, since TSP-1 levels are found upregulated in PAD patients [13, 107].…”
Section: Resultsmentioning
confidence: 99%
“…Although the regulatory roles of TSP-1 in tumor progression is highly cell-type specific, the undesirable anti-angiogenic effect resulting from high TSP-1 expression in PAD is a major interest to cardiologists and vascular biologists [107, 137, 138]. Our model proposed that TGFβ might be an underlying factor driving the high expressions of TSP-1 in PAD patients, given the experimental evidence of TGFβ1 elevation in ischemic tissues [106, 139]. It is interesting to note that hypoxia also upregulates TGFβ1 production in smooth muscle cells in addition to the direct transcriptional induction of TSP-1 via HIFs, suggesting another layer of crosstalk between the pathways that control TSP-1 expression [14].…”
Section: Discussionmentioning
confidence: 99%